2019
DOI: 10.3390/w11030503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Land Uses (Abandoned Farmland, Intensive Agriculture and Forest) on Soil Hydrological Properties in Southern Spain

Abstract: A detailed knowledge of soil water repellency (SWR) and water infiltration capacity of soils under different land uses is of fundamental importance in Mediterranean areas, since these areas are prone to soil degradation risks (e.g., erosion, runoff of polluting compounds) as a response to different hydrological processes. The present study evaluates the effects of land uses on SWR and soil hydraulic conductivity (SHC) by direct measurements at the plot scale in three areas representing (1) intensive agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…The results obtained in this study compare well with other studies conducted elsewhere in the world. For example, a study carried out in Southern Spain on soil hydrological properties in different land uses showed that in intensive agriculture, the soil was more compacted (mean bulk density of 1.25 g/cm 3 ), while in forest, the soil had a lower bulk density (0.83 g/cm 3 ) [37]. Another study [38] done on the soil properties and water infiltration of Andosols in Tenerife (Canary Islands, Spain) found an increase in bulk density in cropped soil compared to the green forest.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in this study compare well with other studies conducted elsewhere in the world. For example, a study carried out in Southern Spain on soil hydrological properties in different land uses showed that in intensive agriculture, the soil was more compacted (mean bulk density of 1.25 g/cm 3 ), while in forest, the soil had a lower bulk density (0.83 g/cm 3 ) [37]. Another study [38] done on the soil properties and water infiltration of Andosols in Tenerife (Canary Islands, Spain) found an increase in bulk density in cropped soil compared to the green forest.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for understanding changes in soil fertility in abandoned lands and the risk of soil degradation. Similarly, more work has to be done on how much soils in abandoned fields are affected by water repellency [82], a phenomenon that decreases infiltration capacity and may explain the high variability of runoff responses in abandoned lands.…”
Section: Open Questionsmentioning
confidence: 99%
“…A lot of research has already been conducted to reveal the impact of SWR on the soil ecosystem under forest and fire‐affected soils (Debano, 2000; Plaza‐Álvarez et al, 2018; Weninger, Filipovi, Me, Clothier, & Filipovi, 2019). However, because the degree of SWR in farmland tillage soil is smaller than the forest and fire‐affected soils (Lucas‐Borja et al, 2019; Stavi, Barkai, Knoll, & Zaady, 2016), there is a lack of research on the SWR in farmland, especially for the study on how conservation agriculture affect SWR. The small degree of SWR, known as subcritical water repellency (Hallett, Baumgartl, & Young, 2001), can also have a considerable effect on soil structure and hydraulic properties (Hunter, Chau, & Si, 2011; Tadayonnejad, Mosaddeghi, & Ghorbani, 2017).…”
Section: Introductionmentioning
confidence: 99%